Mood & Emotion Detection: Whistling Ball Movement Game - C, Shubhangi D; Gadgay, Baswaraj; ., Sushmita (International Journal of Membrane Science and Technology, 2023)
In this investigation, a modified and improved version of the ball-throwing game is presented. The goal is to boost mood and promote mental health utilizing the game system Ball movement and music therapy. The user’s whistle pitch determines how the ball moves in this paper. Whistling can serve as a stimulant for the medical reduction of stress, which makes it useful for rehabilitation. Our algorithm adjusts the ball movement performance dependent on the player’s whistling score after analyzing it. This article focuses on the system’s development and operations.